2008
DOI: 10.1186/1477-7517-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Hookah smoking and cancer: carcinoembryonic antigen (CEA) levels in exclusive/ever hookah smokers

Abstract: BackgroundWe have recently published some work on CEA levels in hookah (also called narghile, shisha elsewhere) and cigarette smokers. Hookah smokers had higher levels of CEA than non-smokers although mean levels were low compared to cigarette smokers. However some of them were also users of other tobacco products (cigarettes, bidis, etc.).ObjectivesTo find serum CEA levels in ever/exclusive hookah smokers, i.e. those who smoked only hookah (no cigarettes, bidis, etc.), prepared between 1 and 4 times a day wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 38 publications
5
61
1
Order By: Relevance
“…smokers in remote villages of the Punjabi countryside who have been smoking only hookah), are in agreement with this chemical fact. 10,11 They are also in agreement with numerous historic studies and recent measurements of biomarkers in body fluids of shisha smokers in Germany. 12 At an international anti-tobacco conference this year, a not yet published study on the levels of many toxic and carcinogenic substances (namely cadmium, lead, chromate, arsenic, metabolites of benzene, polycyclic aromatic hydrocarbons, acrolein, and acrylamide) was announced.…”
Section: Dear Sirsupporting
confidence: 74%
“…smokers in remote villages of the Punjabi countryside who have been smoking only hookah), are in agreement with this chemical fact. 10,11 They are also in agreement with numerous historic studies and recent measurements of biomarkers in body fluids of shisha smokers in Germany. 12 At an international anti-tobacco conference this year, a not yet published study on the levels of many toxic and carcinogenic substances (namely cadmium, lead, chromate, arsenic, metabolites of benzene, polycyclic aromatic hydrocarbons, acrolein, and acrylamide) was announced.…”
Section: Dear Sirsupporting
confidence: 74%
“…Other factors that attract WP smokers, especially adolescents, are its aromatic and condensed smoke, attractive pipe design, availability, inexpensive tobacco, and social acceptance because of traditional associations and it being less stigmatized than cigarette smoking [22]. WP smoking is a new challenge for global public health efforts [23], and recent studies have shown that WP smoke is more harmful than cigarette smoke, because one session of WP smoking expose it's users to a larger amount of smoke and higher level of tobacco toxicants such as tar, carbon monoxide, nicotine, and arsenic compared with one cigarette [24][25][26][27][28][29].WP smoking is considered to be associated with lung cancer, esophageal cancer, low birth weight, periodontal diseases, and pulmonary dysfunction [30].…”
Section: Introductionmentioning
confidence: 99%
“…With this concept, the cancer specific markers CEA, CA 125 and GGT were evaluated in the present study. CEA is a glycoprotein, the elevated levels of which are found in smokers [70] and cervical cancer patients [71]. The enhanced marker level in BaP induced animals indicates the correlation that exists between CEA and tumor burden.…”
Section: Palanisamy and Samiappanmentioning
confidence: 99%